Is insulin resistance play a role in left atrium dysfunction in young hypertensive patients?. (25th November 2020) - Khomova, I.A; Bazdyreva, E.A; Khramkova, A.I; Ezhova, N.E; Shavarova, E; Kobalava, Z.D
Abstract:  : Insulin resistance with normoglycemia could lead to subclinical inflammation, left atrium enlargement and ventricular systolic and diastolic dysfunction. The aim of our study was to analyzed associations between markers of insulin resistance and parameters of left atrium function in young hypertensive patients. Methods: 965 young people were screened, among which 64 (6.6%) had high normal blood pressure and 57 (5.9%) had arterial hypertension. 121 patients with uncomplicated arterial hypertension grade 1–2 were included to the study (81% male, mean age 25.6 (7.3) years, 22 (18%) had obesity, 51 (42%) were smokers). All patients undergone clinical and laboratory evaluation, 24-h blood pressure monitoring, echocardiography. LA function were evaluated by 2D-speckle tracking echocardiography with left atrial reservoir strain (LASr), left atrial booster strain (LASb), left atrial conduit strain (LACs). Insulin level, serum glucose, was measured by using overnight fasting blood sampling between 7 am and 9 am. Insulin resistance was evaluated by HOMA-IR. Results: Mean office systolic BP was 132 [122; 138]; diastolic BP – 70 [63; 76]. LAVI was 23 [19; 27] ml/m 2 . Mean insulin was 8.1 [5.4; 12.3] mIU/l, HOMA-IR – 1.9 [1.2; 2.8]. Correlations between LASr and body mass, waist circumference, insulin level, uric acid, HOMA-IR, E/e', LASb and insulin, HOMA-IR, uric acid, LASc and body mass, waist circumference, insulin level were revealed (p<0.05). Independent association LASc with BMI (B −0.22, p=0.02), LASb with insulin level (B −0.37, p=0.02), LASr with insulin (B −0.37, p=0.02) and with left ventricular (LV) global longitudinal strain (B −0.32, p=0.046) were confirmed in multiple stepwise regression model. Associations between endomyocardial LASb and insulin, HOMA-IR, endomyocardial LASr and body mass, waist circumference, insulin, uric acid, HOMA-IR, E/e', LASra and insulin and HOMA-IR, LASre with body mass, waist circumference, insulin, uric acid, HOMA-IR (p<0.05) were found during correlation analysis. Multiple stepwise regression showed independent associations endomyocardial LASb with HOMA-IR (B −0.44, p=0.005), endomyocardial LASr with HOMA-IR (B −0.46, p=0.003) and with LV global longitudinal strain (B −0.31, p=0.04), LASra with HOMA-IR (B −0.46, p=0.008), LASre with body mass (B −0.48, p=0.036) and with insulin (B −0.38, p=0.001). Conclusion: Left atrium reservoir function is load dependent and influenced by LV function. For subclinical left atrium remodeling assessment booster function should be analized along with reservoir function. In young hypertensive patients insulin level were independently associated with left atrial dysfunction. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Project 5-100